GRAPHITE FURNACE ATOMIC ABSORPTION SPECTROPHOTOMETRY SEBAGAI METODE ANALISIS LOGAM BERAT - Fitri Budiyanto (Pusat Penelitian Oseanografi LIPI, 2017)
GRAPHITE FURNACE ATOMIC ABSORPTION SPECTROPHOTOMETRY AS A METHOD FOR ANALYZING HEAVY METAL. Heavy metal, mostly present in a (ultra) trace-level, becomes one of the hazardous pollutants due to its toxicity, bioaccumulative, biomagnification characters. Conducting a micro analysis of these trace-level pollutants, a sensitive instrument and method are strongly recommended. Graphite Furnace Atomic Absorption Spectrophotometer (GFAAS) offers a solution for the challenge. It uses the principle of light emission absorption by nascent atom cloud from the metals. The analysis has been developed in three stages of the tube heating programs, i.e. drying, ashing and then atomizing element at 3000° C. Since the injected sample is almost completely atomized, the sensitivity of GFAAS is extremely high and this value is covering up the disadvantages of the other analyses. Therefore, the GFAAS analysis is suitable fo ultra-trace analysis of ultra-trace pollutants like heavy metals in environment.